The Impact of Subjective Norms and Entrepreneurship Education on Student Entrepreneurial Intentions - Bayu Kurniawan; Mita Umitahrizah; Qristin Violinda (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
This study aims to measure the effect of subjective norms, entrepreneurship education, on student entrepreneurial intentions mediated by self-efficacy. This paper proposes a resolution to these discrepancies and tests these hypotheses in a university setting. This type of research is quantitative research, which uses a research instrument in the form of a questionnaire that has been compiled I n several statements and is measured using a Likert scale of 1-5. The population used in this research is the 2020-2022 Management Study faculty of economic and business. The sampling technique used the Cochran formula which obtained 309 samples. This study uses Structural Equation Modeling (SEM) which is run through AMOS 24 as an analysis tool. The results of the hypothesis test show that subjective norms have an effect on entrepreneurial intentions, while the entrepreneurship education variable has an effect on entrepreneurial intentions. Subjective norms affect entrepreneurial intentions mediated by self-efficacy. While very insightful, this paper is limited by the use of a within-subjects survey research design and the inherent limitations with such research. Additionally, using college students as respondents limits the ability to generalize the results to any population outside similar college-age populations. Keywords: entrepreneurial intentions, subjective norms, entrepreneurship education, self efficacy, student